2010
DOI: 10.1242/jeb.048611
|View full text |Cite
|
Sign up to set email alerts
|

Diel foraging behavior of gravid leatherback sea turtles in deep waters of the Caribbean Sea

Abstract: SUMMARYIt is generally assumed that leatherback turtles (Dermochelys coriacea), like other species of sea turtle, do not feed while offshore from nesting beaches, and rely instead on fat reserves to fuel reproductive activities. Recent studies, however, provide evidence that leatherbacks may forage during the internesting interval while offshore in the Western Atlantic Ocean and Caribbean Sea. Bio-logging technology was used to investigate the foraging behavior of female leatherback turtles at St Croix, US Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 58 publications
3
37
1
Order By: Relevance
“…The diel cycle has been reported elsewhere for leatherbacks during southward migrations and v www.esajournals.org while resident in the tropics (Eckert et al 1989, James et al 2005a, James et al 2006a, Casey et al 2010. However, only with the HR archival data presented here is the consistency so clearly evident for turtles in their Canadian foraging domain, and so clearly triggered by solar illumination.…”
Section: Dive Frequency Variationsupporting
confidence: 75%
See 4 more Smart Citations
“…The diel cycle has been reported elsewhere for leatherbacks during southward migrations and v www.esajournals.org while resident in the tropics (Eckert et al 1989, James et al 2005a, James et al 2006a, Casey et al 2010. However, only with the HR archival data presented here is the consistency so clearly evident for turtles in their Canadian foraging domain, and so clearly triggered by solar illumination.…”
Section: Dive Frequency Variationsupporting
confidence: 75%
“…Heaslip et al (2012) demonstrated that foraging during daylight hours in Atlantic Canada is restricted to the photic zone. Moreover, while leatherbacks clearly dive throughout the night throughout their range, Casey et al (2010) provide evidence from stomach temperature telemetry that food ingestion rates in waters adjacent nesting beaches are significantly lower during the night than during the day.…”
Section: Dive Frequency Variationmentioning
confidence: 75%
See 3 more Smart Citations